Kolaborasi Pemerintahan untuk Meningkatkan Daya Saing Tenaga Kerja Melalui Program Handak Begawi di Kota Bontang - Siti Mutoharoh; Agus Prastyawan; Daryono (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Bontang City Government through the Manpower Office launched the Handak Begawi Program. The program is an effort to collaborate companies in Bontang City, vocational training centers and vocational training institutions in order to play an active role in improving the competitiveness of the workforce. This research used a qualitative approach. Data was collected by interviews, observation, and documentation. From the theory of Collaborative Governance by Anshell and Gash (2007), the results of the study are divided into four variables, namely initial conditions that have gone well, clear and consistent institutional design, but for facilitative leadership and collaboration processes are still not optimal. Supporting factors for the implementation of this government collaboration are the existence of a cooperation agreement, the existence of a vision and mission and work program in the collaboration process, trust between stakeholders, collaboration actors get the same opportunities, the decision-making process and sharing responsibilities have also been running, the provision of information data in the collaboration process has been carried out in an organized manner and according to the needs of the collaboration actors, and appropriate resources are available. Inhibiting factors occur due to the lack of socialization related to training and apprenticeship rules, less than optimal facilitative leadership, the absence of regular meetings, and the limited needs of apprentices from employers. Overall, the implementation of government collaboration in the Handak Begawi Program has gone well in accordance with the success factors described by De Seve in government collaboration.